Pesan Dakwah dalam Q.S. Ar-Ra’d [13]: 11 Ditinjau dari Penafsiran Klasik-Kontemporer - Rahman, Muhammad Iqbal; Erdiyansyah, Erdiyansyah (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Q.S. Ar-Ra'd [13]: 11 is a verse familiar to Muslims, including Muslims in Indonesia. This is reflected in the many texts that quote, explain, and translate Q.S. Ar-Ra'd [13]: 11 on various platforms, both online and offline media. However, some motivators only convey snippets of the verse without knowing the real meaning of the verse. This impacts the public's understanding as an audience who considers Q.S. Ar-Ra'd [13]: 11 to be a motivational verse, differing in opinion from commentators in general. Therefore, this article raises the main issue,